Controle postural em condições de manipulação de tarefa em crianças e adolescentes com paralisia cerebral - Costa, Laís da Cruz Reis (2021)
Postural control is important for independence in the daily activities of children and adolescents and is dependent on the interaction between the visual, somatosensory and vestibular systems. In addition, the sensory system modifies the efferent motor command, regulating the musculoskeletal system, to promote voluntary and automatic actions, modulating postural control according to the demands of the environment. However, individuals with cerebral palsy (CP), as a result of lesions in the central nervous system, have motor deficits and sensory information processing deficits, which impair postural control. In many everyday situations, in which sensory inputs are reduced, such as in low light conditions and without support for the upper limbs, there may be an exacerbation of the difficulty in postural control, thus increasing the risk of falls. In view of this, the motivation to develop a systematic review arose, in order to verify sensory manipulation and synthesize its influence on postural control, updatinganexistingsystematic review. Thus, a study was carried out, entitled ''Sensory manipulation and postural control in individuals with cerebral palsy: A systematic review''. It was found that sensory manipulation can facilitate postural control when an additional visual stimulus is used, or it can cause harm when sensory information is restricted/reduced, however, the included studies did not investigate how muscle activation patterns occur, in association with the behavior of the center of pressure, during the manipulation of different sensory information. After the finalization and interpretation of the review, gaps were noticed regarding the topic and the population of interest. In this way, study II was prepared, entitled ''Postural Control in conditions of task manipulation in children and adolescents with Cerebral Palsy'' emerged, in which typical and typical children and adolescents with CP were evaluated, in order to verify the effect of four conditions (open eye with support; open eye with out support; closed eye with support and closed eye without support) on postural sway, assessed by the displacement of the center of pressure, in orthostatism; and on muscle activation, assessed by RMS and co-contraction, of the lower limbs and trunk. The results showed that the group with CP presented greater postural sway than the typical group, in all conditions evaluated. Furthermore, in the evaluation of muscle activation, it is noted that the CP group uses different strategies than the typical group to maintain postural control. Thus, these studies contribute to rehabilitation professionals, leading to reflections on how to use the manipulation of task conditions both to facilitate and to challenge postural control, depending on the objective of the therapy.